Foreign language teachers’ perceptions of observational feedback - Oldham, Seth (Kansas State University, 2016)
Though the subject of recent national attention and various in-depth investigations, the most effective approach to teacher evaluation in the United States is still an issue of debate. The latest research focuses on evaluation of teachers of core content areas like math, science and reading, but evaluation of foreign language teachers and programs receives comparatively little attention in the literature. This study examines issues related to observational feedback particular to the foreign language teaching context using data collected from teachers and administrators in large public school districts in Kansas. Survey data reveals that while public school foreign language teachers are generally satisfied with observational feedback concerning classroom behaviors, such as teacher-student interaction and behavior management, they often report receiving no feedback in the areas of curriculum planning or instructional techniques particular to their content area. Administrators report focusing on preparedness and classroom management during observations. Gaps identified in observational feedback are discussed and changes to observation practices are suggested.
Keywords: Foreign language education; Educational evaluation; Secondary education; Teacher observation